PytanieZapisz wyrażenie, nie uzywając nawiasów. Zredukuj wyrazy podobne.
6x-(3+5x)=
3+(8a-5)-(5a+2)=
5a+3b-5-(2a-3b-5)=
2a+(3a-2b)+(a+b)=
5x+3y+(2y-4z)-(5y+6z)=
-2c+4-(3c+2d)-(5d-2)=


Odpowiedź :

Odpowiedź:

6x - (3 + 5x) = 6x - 3 - 5x = x - 3

3 + (8a - 5) - (5a + 2) = 3 + 8a - 5 - 5a - 2 = 3a - 4

5a + 3b - 5 - (2a - 3b - 5) = 5a + 3b - 5 - 2a + 3b + 5 = 3a + 6b

2a + (3a - 2b) + (a + b) = 2a + 3a - 2b + a + b = 6a - b

5x + 3y + (2y - 4z) - (5y + 6z) = 5x + 3y + 2y - 4z - 5y - 6z = 5x - 10z

- 2c + 4 - (3c + 2d) - (5d - 2) = - 2c + 4 - 3c - 2d - 5d + 2 = - 5c - 7d + 6